AN ISLAMIC SEARCH OF NOBLE VALUES: THE PREVALENCE OF MODERN PRINCIPLES AND THE RESILIENCE OF LOCAL TRADITIONS IN INDONESIAN DA‘WA - Suwarno, Peter (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
The variety of da‘wa (Islamic preaching) in Indonesia indicated not only the diversity in Islamic groups and identities, but also the varieties and changes in values and principles embraced by Indonesian Muslims. This paper argued that these da‘wa activities constitute searches of most suitable Indonesian Islamic principles that inevitably include the negotiation of Islamic, global, and local values. For this purpose, this paper showed examples of various international and Indonesian Islamic scholars and leaders who help change social, political, and religious rhetorical landscape through various arguments involving especially Islamic and modern-international values. This paper maintained that, in addition to Muslims exposure to modern global principles such as democracy and human rights, the increasing popularity and resilience of local-traditional rituals, performances, and expressions in Indonesian da‘wa have significantly shaped the search of the Indonesian Islamic noble values.***Keragaman dakwah Islam di Indonesia tidak hanya tampak dalam keragaman kelompok serta identitas Islam, tetapi juga dalam varian dan perubahan nilai-nilai serta prinsip-prinsip yang dianut oleh umat Islam Indonesia. Tulisan ini menegaskan bahwa kegiatan dakwah ini merupakan pencarian prinsip-prinsip Islam Indonesia yang paling sesuai yang mau tidak mau merupakan upaya negosiasi nilai Islam, global, dan nilai-nilai lokal. Untuk tujuan tersebut, tulisan ini menunjukkan beberapa contoh ulama dan pemimpin Islam internasional dan Indonesia yang membantu mengubah landscape retorika sosial, politik dan agama melalui berbagai argumen yang secara khusu melibatkan nilai-nilai Islam dan modern-internasional. Tulian ini berpendapat bahwa, disamping Muslim harus berhadapan dengan prinsip-prinsip global modern seperti demokrasi dan hak asasi manusia, meningkatnya popularitas dan ketahanan dari ritual,  pertunjukan, dan ekspresi lokal-tradisional dalam dakwah Indonesia telah membentuk pencarian nilai-nilai luhur Islam Indonesia secara signifikan.